HUBUNGAN PERSEPSI DENGAN PERILAKU IBU HAMILTRIMESTER I DALAM MENGATASI EMESIS GRAVIDARUM DI WILAYAH KERJA PUSKESMAS PAYUNG SEKAKI KOTA PEKANBARU TAHUN 2021 - Melati Trysiana Pasaribu; Widia Lestari; Erika Erika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Emesis gravidarum is nausea and vomiting that often occurs in the group of early trimester pregnant women. This goal of the study was to determine the relationship perceptions with behavior of pregnant women in overcoming emesis gravidarum. The goal of this study used a descriptive correlation with cross sectional. The sample in this study were 47 first trimester pregnant women who were taken based on approach inclusion criteria using purposive sampling technique. The analysis used was bivariate and univariate analysis using the chi-square test. That all pregnant women are at the age of 20-35 years, namely 47 respondents (100%), most of the respondents based on education found high school students as many as 30 people (63.8%), most of the respondents were found is Malay as many as 19 people (24.7 %), then pregnant women with primigravida parity as many as 29 people (61.7%) and based on respondents based on their husband's workplace, most of them are husbands who work in the city as many as 42 people. people (89.4%). The results of statistical tests showed that there was a significant relationship between the perception with behavior of pregnant women in overcoming emesis gravidarum p value (0.002) < (0.05). There is a relationship  perception with the behavior of pregnant women in the first trimester in overcoming emesis gravidarum.Keywords: Emesis Gravidarum, Perception, Behavior